Alternative VPN Solution Using Raspberry Pi as Router - Dziaudin, Shah Khairul Hakem; Mohd Salleh, Hilmi (Journal of Computing Technologies and Creative Content, 2020)
Free Wi-Fi is exceptionally convenient to the public, but security can be a concern as such free access points are available at restaurants, hotels, airports, and cafes. Even though it has a router firewall, it does not mean that the network is shielded from certain network connections. It is incredibly easy to steal the username and password of others or see what they do by using the same network. The big challenge to free Wi-Fi security is the hackers’ ability to position themselves between the user and the link point. The hacker steals information that you send on the Internet, such as valuable e-mails, credit card data, and personal information. The aim is to create a Virtual Private Network (VPN) Router using Raspberry Pi. VPN works to protect the Internet connection of the user’s device to ensure that all data sent and received is authenticated and protected. The VPN router is based on the most popular Raspberry Pi 3 on the market, allowing people to avoid Wi-Fi attacks of this type without installing any program or application on their devices. This makes the router a link between the user and public network and allows the connection of several client devices to this router. The router has been checked to ensure that this VPN router provides the best speed and durable protection. Finally, we hope that the VPN router will help secure internet connections and protect their privacy.